UV Light Acclimation Capacity of Leaf Photosynthetic and Photochemical Behaviour in Near-isohydric and Anisohydric Grapevines in Hot and Dry Environments - Fernandes de Oliveira, A.; Rais, F.; Dettori, I.; Azzena, M.; Nieddu, G. (South African Journal of Enology and Viticulture, 2019)
The photosynthetic and photochemical adaptation of grapevine leaves to high UV radiation, under hot and dry summer conditions, was investigated in near-isohydric Cannonau (syn. Grenache) and nearanisohydric Bovale grande (syn. Carignan). From pea-size stage until harvest, vines with mild to moderate water deficit were subjected to UV-blocking treatment (–UV) and compared to a control exposed to sunlight (C). Canopy light and thermal microclimate, growth and density, maximum leaf gas exchange, primary photochemistry (PSII) and phenols were monitored. Average increments in canopy temperature under –UV tunnels during day-time and night-time were 3.3°C and 0.8°C in Bovale grande and 2.6°C and 1.1°C in Cannonau. Cultivars reached similar leaf area, intrinsic water-use efficiency and stem water potential under C and –UV. Cannonau showed lower stomatal conductance, maximum net assimilation and transpiration rates, but also faster recovery of PSII under heat and moderate water stress. UV radiation induced a stronger and longer impact on leaf assimilation, but the duration of elevated temperatures under −UV induced higher photoinhibition and lower photochemical efficiency. A similar degree of correlation between leaf temperature and gas exchange was found among cultivars and treatments. In Cannonau, leaf anthocyanin decreased due to heat-induced long-lasting PSII photoinactivation under C. Conversely, Bovale grande showed higher phenolic content stability, thus higher photoprotection and recovery of PSII functional units. Agronomical practices affecting leaf phenolic accumulation influence canopy acclimation to heat and high sunlight. Vineyard management must avoid excessive canopy sun exposure and duration of elevated temperatures to favour high assimilation, while reducing photoinactivation and heat damage.